2020
DOI: 10.3390/ani10030399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Management Strategies on Non-Beak-Trimmed Laying Hens in Furnished Cages that Were Reared in a Non-Cage System

Abstract: Beak trimming in laying hens limits the negative consequences of injurious pecking, but could be prohibited by future regulations. This study assessed a combination of management strategies during the rearing period (objects, perches, music, human presence) and laying period (scratching mats, objects, feed fiber supplementation) to raise non-beak-trimmed animals. The welfare and laying performances of beak-trimmed (T) and non-beak-trimmed (NT) ISA Brown birds were compared between groups with (E) or without (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In contrast, Guinebretière et al. (2020) showed that an artificial turf mat placed on the furnished cage floor and different objects hooked onto the cage façade (10 small mobile and coloured objects, plastic transparent pots filled with coloured rings and plastic chain links for a cage housing 60 hens) reduced feather cover damage.…”
Section: Assessmentmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, Guinebretière et al. (2020) showed that an artificial turf mat placed on the furnished cage floor and different objects hooked onto the cage façade (10 small mobile and coloured objects, plastic transparent pots filled with coloured rings and plastic chain links for a cage housing 60 hens) reduced feather cover damage.…”
Section: Assessmentmentioning
confidence: 95%
“…The specificity is high, as it is highly unlikely that bruises will be detected in birds not affected by this welfare consequence. (Ratner and Thompson, 1960;Jones and Waddington, 1992;Cotter, 2015), the novel arena test (also known as open field test), the novel object test (Welfare Quality, 2009), the human approach test, or the emergence test (Forkman et al, 2007) and avoidance distance test (Whay et al, 2007;Guinebreti ère et al, 2020). Often, a combination of several tests is used.…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…Although no strategy can guarantee the complete absence of pecking behaviours, optimised management practices, especially concerning feeding, lighting, and climatic conditions [35] and environmental enrichment in pullets and adult birds [61][62][63], can help to reduce the risk. Access to outdoor free-range areas is associated with plumage preservation [6,7,64] and a reduced risk of injurious pecking [65].…”
Section: Main Causes Of Damaging Behaviour and Control Strategiesmentioning
confidence: 99%
“…This objectively expands the space for each hen to move freely and alleviates the frustration caused by a lack of space [ 81 ], leading to a significant improvement in their welfare. At the same time, the forest land may contain abundant natural food, which is beneficial for laying hens to show normal foraging behaviours and avoid being subjected to beak trimming, which is common in cage systems [ 82 ]. Most importantly, considering the most critical woodland resources for understory laying hen system, the majority of farmers have relatively low use costs.…”
Section: Challenges and Solutions To The Free-range Systemmentioning
confidence: 99%